PENGARUH PEMBELAJARAN MODEL ADVANCE ORGANIZER TERHADAP HASIL BELAJAR BIOLOGI SISWA PADA KONSEP PROTISTA - Nuri Shabania; Yuke Mardiati; Ahmad Sofyan (EDUSAINS, 2015)
This research purposed  to know the influence of using advance organizer model to students’ biology achievement in protists concept. This research was used quasi experiment method with pretest-posttest control group design. The data analysis was used t-test, from the result of calculating mean differentiation of posttest both groups, obtained the value of t-count was equal to 3,087, while t-table at the level of significant 5% with degree of freedom (df) = 78 that was equal to 1,67. So, it can be said that t-count > t-table that means the alternative hypothesis (Ha) was accepted and the zero hypothesis (H0) was refused. It showed that there was influence of using advance organizer model to students’ biology achievement in protists concept.